Edukasi Rumah Sehat melalui SKK Krida Bina Lingkungan Sehat bagi Anggota SBH Kapanewon Bambanglipuro - Selvia Tri Kurnia; Darum Sidiq Setya Pangarsa; Afrizal Safrin Nadifa; Ibnu Rois; Yunita Dwi Astuti; Ambarwati Widadaning Astuti (Jurnal Abdimas Kesehatan (JAK), 2026)
A healthy home is a living environment that supports occupants’ health through clean surroundings, adequate ventilation and lighting, and proper sanitation. In contrast, unhealthy housing conditions often fail to meet health standards and may increase the risk of environment-related diseases. One effort to address this issue is through the role of Saka Bakti Husada as a form of Community-Based Health Effort that focuses on improving health knowledge and awareness. This community service activity aimed to measure the level of knowledge of Saka Bakti Husada members regarding the concept of a healthy home after a socialization program conducted at SMA Negeri 1 Bambanglipuro. The activity was implemented using an educational approach through counseling methods, accompanied by knowledge assessment using pre-test and post-test. The evaluation involved 20 respondents out of a total of 33 participants. The results showed a significant improvement in participants’ knowledge, with an average pre-test score of 11.80 and a post-test score of 18.25 (p < 0.05). These findings indicate that the socialization activity was effective in increasing participants’ understanding of the healthy home concept. Therefore, schools are encouraged to strengthen the guidance of Saka Bakti Husada by integrating this activity into regular scouting programs, with support from community health centers in providing educational materials and technical assistance in environmental health.